Manufacturing and compatibilization of binary blends of superheated steam treated jute and poly (lactic acid) biocomposites by melt-blending technique. Issue 8 (August 2022) - Alim, Md. Abdul; Moniruzzaman, Md.; Hossain, Md. Muzaher; Wahiduzzaman,; Repon, Md. Reazuddin; Hossain, Ismail; Jalil, Mohammad Abdul
Abstract: This work investigated the effect of superheated steam (SHS) jute fiber and poly (lactic acid) (PLA) having a weight proportion of 30:70 which were synthesized using the melt blending method. The goal of this treatment was to boost up the fiber-polymer interfacial linkage. The action was conducted in a superheated steam oven at various times (30–120 min) and temperatures (170–220 °C). The biocomposites were assessed in terms of mechanical characteristics, dimensional stability and morphological properties. Compared to different treatment temperatures, the results showed that treatment at 210 °C for 60 min offered the best tensile characteristics. Because of the presence of SHS-Jute, the tensile, impact, bending and dimensional stability of the bio-composites have been improved. The FTIR and SEM study revealed progress in the interfacial linkage between SHS-Jute and PLA. This interfacial link improves the bending strength of SHS-Jute-PLA biocomposites by about 15.64%. X-ray diffraction (XRD) investigation also showed an elevation in the crystalline structure with the incorporation of SHS-Jute. The degradation tests of the biocomposite were carried out in deionized water. SHS treatment reduces hemicellulose contents in jute fiber which causes water uptake% reduction is 54% in SHS-Jute-PLA. The SHS-Jute-PLA biocomposite appeared with promising characteristics for utilization as a green and ecological substitute particle board material. Abstract : Biocomposite; Jute fiber; Poly (lactic acid); Superheated steam; Swelling.